A Gastric Cancer Peptide GX1-Modified Nano-Lipid Carriers Encapsulating Paclitaxel: Design and Evaluation of Anti-Tumor Activity - Jian Y; Zhao M; Cao J; Fan T; Bu W; Yang Y; Li W; Zhang W; Qiao Y; Wang J; Wen A (Dove Medical Press, 2020)
Yufan Jian,1,2,* Meina Zhao,1,2,* Jinyi Cao,1,* Tingting Fan,1 Wei Bu,1 Yang Yang,3 Weiwei Li,1 Wei Zhang,1 Yi Qiao,1 Jingwen Wang,1 Aidong Wen1,2 1Department of Pharmacy, Xijing Hospital, The Fourth Military Medical University, Xi’an 710032, People’s Republic of China; 2College of Pharmacy, Shannxi University of Chinese Medicine, Xianyang 712046, People’s Republic of China; 3Institute of Medical and Pharmaceutical Sciences, Zhengzhou University, Zhengzhou 450001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tingting Fan; Aidong WenDepartment of Pharmacy, Xijing Hospital, The Air Force Military Medical University, Xi’an 710032, People’s Republic of ChinaEmail fanting0427@163.com; adwen-2004@hotmail.comAim: The aim of this study was to develop a GX1-modified nanostructured lipid carrier (NLCs) and to evaluate its ability to improve the anti-gastric cancer tumor effects of paclitaxel (PTX).Main Methods: The GX1-modified NLCs were synthesized and loaded with PTX (GX1-PTX-NLCs) by emulsion solvent evaporation technique. The anti-tumor activity and pharmacodynamics were then evaluated by in vitro cell studies and animal experiments.Key Findings: The GX1-modified NLCs were successfully synthesized and confirmed by 1H NMR and MALDI-TOF-MS. PTX-loaded NLCs produced particles with average size distribution less than or equal to 222 nm and good drug loading and entrapment efficiency. In vitro studies demonstrated that GX1-PTX-NLCs had a more obvious inhibitory effect on Co-HUVEC cells than PTX and unmodified PTX-NLCs. The cellular uptake results also showed that GX1-PTX-NLCs were largely concentrated in Co-HUVEC cells, and the uptake rates of GX1-PTX-NLCs in Co-HUVEC were higher than those of the free drug and the PTX-NLC. In vivo studies demonstrated that GX1-PTX-NLCs possess strong anti-tumor effect and showed higher tumor growth inhibition and lower toxicity in nude mice.Significance: These results suggest that GX1-modified NLCs enhanced the anti-tumor activity of PTX and reduced its toxicity effectively. GX1-PTX-NLCs may be considered as a potent drug delivery system for therapy of gastric cancer.Keywords: gastric cancer, paclitaxel, nano-lipid carriers, gastric cancer peptide, anti-tumor activity